BETTANG PANJANG LOCAL WISDOM AS SELF-IDENTITY (Ethnographic Study in Betang Panjang, Ensaid Panjang Village, Kelam Permai District, Sintang Regency) - Karnodin; Pether Sobian; Agus Sanjaya (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Local wisdom is a self-identity that should be maintained, protected and passed down to the next generation, because local wisdom is the identity of a community. There are quite a lot of Dayak communities that have lost their local wisdom, so the author feels the need to conduct research on the sustainability of local wisdom in Bettang Panjang, Ensaid Panjang Village, a longhouse inhabited by a small part of the Dayak Dessa sub-tribe. Local wisdom is an identity that must be maintained and passed down to the next generation, that is the self-identity believed by the Dayak Dessa sub-tribe community who live in Bettang Panjang in Ensaid Panjang Village, Kelam Permai District, Sintang Regency. Local wisdom is the values of personal life, communal life and the environment, norms, traditions, and spiritual practices maintained in the community that inhabits Bettang Panjang. This local wisdom becomes the identity or distinguishes the Dayak Dessa sub-tribe community from other communities, this is because the residents of Bettang still maintain and practice most of the local wisdom of the Dayak Dessa sub-tribe from generation to generation. This local wisdom is what becomes the identity of the Dayak Dessa sub-tribe community who inhabit Bettang Panjang. This local wisdom is a characteristic that distinguishes the Dayak Dessa sub-tribe from other Dayak sub-tribes in the surrounding area.